Bronchogenic Cyst in Posterior Mediastinum with Butterfly Vertebra: A Case Report - Myeongjong Kim; Hyun Jin Park; Jeong Min Ko; Jinyoung Yoo (대한영상의학회지, 2019)
Most mediastinal cystic masses result from abnormal development of the embryo. Common developmental cysts in the posterior mediastinum are bronchogenic, neurenteric, and esophageal duplication cysts. These cystic masses appear identical on CT, but a cystic lesion adjacent to the esophagus is usually an esophageal duplication cyst, and a cyst associated with vertebral anomalies indicates a presumptive diagnosis of a neurenteric cyst. Herein, we present the case of a 27-year-old man with a bronchogenic cyst in the posterior mediastinum with a butterfly vertebra.